Experimental application of waste glass powder filler in recycled dense-graded asphalt mixtures. Issue 3 (3rd April 2019) - Simone, Andrea; Mazzotta, Francesco; Eskandarsefat, Shahin; Sangiorgi, Cesare; Vignali, Valeria; Lantieri, Claudio; Dondi, Giulio
Abstract : This paper presents laboratory study results, including both bituminous mastics and mixtures tests, to assess the use of glass powder (GP) as possible surrogate to limestone filler in recycled dense-graded asphalt mixtures. To achieve a comprehensive approach, the analysis has been divided into three parts including filler, mastics and mixture characterisation. The GP has been completely studied with chemical and physical tests to compare the fundamental characteristics to the commonly used limestone filler. In the second part, rheological tests using the Dynamic Shear Rheometer has been implemented to evaluate fillers interaction with not modified and modified bitumen. Finally, the mechanical properties of the asphalt mixtures containing GP filler were investigated in terms of indirect tensile strength, indirect tensile stiffness modulus and creep characteristics. According to the obtained results, GP filler provided comparable values to limestone filler within both mastic and mixture study. It is noteworthy that from the permanent deformation analysis, both MSCR and RLAT tests confirmed the improvement of rutting resistance with using GP filler.